Chromatography : fundamentals and applications of chromatography and related differential migration methods. - Heftmann, Erich (Journal of chromatography library, 2004)
Chromatography has emerged as the most important and versatile analytical method. The book is not only an updated version of Heftmann's classical text, but it covers areas of future importance, such as microfluidics and computer resources. Under his experienced guidance, authorities in each field have contributed their practical experience to an integrated treatment of modern micro analysis. In Part A the theoretical basis of individual separation methods is explained and the technical aspects are illustrated. It includes the theory of gas and liquid chromatography as well as specific chromatographic techniques, such as size-exclusion, planar, ion, and affinity chromatography as well as various electrokinetic separation techniques. Microfluidics are covered for the first time and useful sources of analytical instruments are listed and evaluated. 1. Each chapter written by an authority 2. Thorough treatment of the theoretical basis of separation methods 3. Practical guide for performing analyses.